2019
DOI: 10.1136/bmjopen-2018-024194
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma B-type natriuretic peptide and anaemia in heart failure with or without ischaemic heart disease: a retrospective study

Abstract: ObjectivesAnaemia is a risk of worsening heart failure. However, anaemia sometimes remains undetected because the superficial cardiac function does not precisely reflect the adverse impact of anaemia. Plasma B-type natriuretic peptide (BNP) could be helpful in these cases. However, the direct anaemic effects on BNP remain unknown. Herein, we compared the direct effect of anaemia on BNP and left ventricular ejection fraction (LVEF) using an advanced statistical procedure.DesignA retrospective study.SettingSecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…On the other hand, a study found that after examining patients with heart failure, there was an inverse relationship between both BNP and Hb level. Despite the fact that it is expected to find an elevation in the BNP level, nevertheless, their reported value for correlation coefficient (r) between both variables was close to that reported by this study (0.41 vs 0.39) [13].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, a study found that after examining patients with heart failure, there was an inverse relationship between both BNP and Hb level. Despite the fact that it is expected to find an elevation in the BNP level, nevertheless, their reported value for correlation coefficient (r) between both variables was close to that reported by this study (0.41 vs 0.39) [13].…”
Section: Discussionsupporting
confidence: 80%
“…Our results support recommendation to carefully investigate the causes of anaemia in HF patients, especially the potentially reversible ones (e.g., iron deficiency, chronic bleeding, and medications) [1,24]. It is suggested that the treatment for anaemia should be initiated at an early stage before systolic function begins to decline [4]. Intravenous iron infusions seem to be the most efficient therapy for anaemia in HF.…”
Section: Discussionsupporting
confidence: 74%
“…e haemodynamic response to tissue hypoxia induced by severe anaemia in patients without cardiac disease presents as tachycardia, high cardiac output induced by the activation of the sympathetic nervous system, low vascular resistance caused by generalised vasodilation, and fluid retention [3][4][5]. In extreme cases, it can manifest as "noncardiac circulatory congestion" with pulmonary oedema and hypotension [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations